PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KINERJA PADA PT PLN UP3 BANTEN SELATAN - Zakiyya Tunnufus; Illa Kurnia Asih (The Asia Pacific Journal Of Management Studies, 2022)
Employee performance is an important foundation for the company. Generally, companies always want their employees to have good performance or work performance to achieve the company's goals. The level of success of the company depends on employee performance. One of the efforts to improve employee performance is by paying attention to individual characteristics and work environment. The research method that I use in this research process is to use quantitative methods. The population in this study amounted to 60 people. The sampling technique used in this study is a non-probability sampling technique with a saturated sampling method. Collecting data in this study using observation techniques, literature study, questionnaires and documentation. The analysis technique in this study used the normality test, autocorrelation test, heteroscedasticity test and multicolonierity test. Hypothesis testing in this study used multiple linear regression, correlation coefficient analysis, determination coefficient test, t test and F test processed with the SPSS 21 program. The results showed that both partially and collectively individual characteristics and work environment had a positive and significant effect on employee performance. The dominant variable that affects employee performance is the work environment. The contribution of individual characteristics and work environment variables to employee performance is 21.3% and the rest is contributed by other variables not examined. Meanwhile, both partial and simultaneous individual characteristics and work environment have a positive and significant effect on employee performance..